A brief review of current sea ice numerical models and sea ice modelling through two-way ocean-sea ice coupled model - XU, XINGKUN; Nose, Takehiko; Fujiwara, Yasushi; Kodaira, Tsubasa; Waseda, Takuji (2022)
The 13th Symposium on Polar Science/Interdisciplinary sessions [IA] Arctic research, Thu. 17 Nov. conference object